(untitled) (Bioresearch Communications, 2026)
Microbial diversity plays a crucial role in ecosystem functioning and biogeochemical processes. However, bacterial diversity in the Moheshkhali Channel, Bay of Bengal, Bangladesh, remains largely unexplored and this study aimed to investigate the bacterial diversity from seawater and sediment sample. Seawater and sediment samples were collected from the Moheshkhali Channel, and physicochemical parameters, including Environment temperature (35˚C) Seawater Temperature (33˚C), pH=7, and dissolved oxygen (7.13 mg/L), were measured in situ. Bacteria were isolated using standard microbiological techniques under aseptic conditions and cultured on LB Agar media. A total of six morphologically distinct bacterial isolates were obtained Gram staining confirmed that all isolates are gram positive and majority bacterial strain are rod-shaped bacteria. Biochemical identification using the VITEK® 2 Compact system identified two isolates as Leuconostoc mesenteroides subsp. cremoris and Aerococcus viridans. The others isolates were unidentified or low-reactive biopatterns. biochemical data show that all bacteria isolates were metabolically different. Bioresearch Commu. 12(2): 2130-2135, 2026 (January)